Herpes simplex virus origin-binding protein (UL9) loops and distorts the viral replication origin. - Koff, A (1991)
To investigate the role of the herpes simplex virus origin-binding protein (UL9) in the initiation of DNA replication, we have examined the effect of UL9 binding on the structure of the viral origin of replication. UL9 loops and alters the DNA helix of the origin regardless of the phasing of the binding sites. DNase I and micrococcal nuclease footprinting show that UL9 binds two sites in the origin and loops the AT-rich DNA between them independent of the topology of the DNA. KMnO4 and dimethyl sulfate footprinting further show that UL9 alters the DNA helix in the AT region. In contrast to the looping reaction, however, helical distortion requires the free energy of supercoiled DNA. UL9 also loops and distorts the origin DNA of a replication-defective mutant with a 6-bp insertion in the AT region. Because the helical distortion of this mutant DNA is different from that of functional origins, we conclude that an imperfect tertiary structure of the mutant DNA may contribute to its loss of replication function.